Comprehensive global collaboration in the care of 1182 pediatric oncology patients over 12 years: The Iraqi–Italian experience. (3rd June 2022) - Al‐Jadiry, Mazin Faisal; Uccini, Stefania; Testi, Anna Maria; Moleti, Maria Luisa; Alsaadawi, Adil Rabeea; Al‐Darraji, Amir Fadhil; Al‐Saeed, Raghad Majid; Faraj Al‐Badri, Safaa A.; Sabhan, Ahmed Hatem; Ghali, Hasanein Habeeb; Fadhil, Samaher Abdulrazzaq; Abed, Wisam Majeed; et al.
Abstract: Background: Iraq's health care system has gradually declined after several decades of wars, terrorism, and UN economic sanctions. The Oncology Unit at Children's Welfare Teaching Hospital (CWTH) in Baghdad was lacking basic facilities and support. To address this shortcoming, a humanitarian and educational partnership was established between CWTH and Sapienza University of Rome (SUR). Methods: We investigated the outcomes of 80 online and 16 onsite educational sessions and 142 teleconsultation sessions from 2006 to 2014. We also determined the outcomes of pathology reviews by SUR of 1216 tissue specimens submitted by CWTH from 2007 until 2019 for second opinions. The primary outcomes were discordance, concordance, and changes among clinical diagnoses and pathology review findings. The measures included the frequency of teleconsultation and tele‐education sessions, the topics discussed in these sessions, and the number of pathology samples requiring second opinions. Findings: A total of 500 cases were discussed via teleconsultations during the study period. The median patient age was 7 years (range, 24 days to 16·4 years), and the cases comprised 79 benign tumors, 299 leukemias, 120 lymphomas, and 97 solid tumors. The teleconsultation sessions yielded 27 diagnostic changes, 123 confirmed diagnoses, and 13 equivocal impacts. The pathology reviews by SUR were concordant for 996 (81·9%) cases, discordant for 186 (15·3%), and inconclusive for 34 (2·8%). The major cause of discordance was inadequate immunohistochemical staining. The percentage of discordance markedly decreased over time (from 40% to 10%). The cause of the improvement is multifactorial: training of two CWTH pathologists at SUR, better immunohistochemical staining, and the ongoing clinical and pathologic telemedicine activities. The partnership yielded 12 publications, six posters, and three oral presentations by CWTH investigators. Interpretation: The exchange of knowledge and expertise across continental boundaries meaningfully improved the diagnoses and management of pediatric cancer at CWTH. Abstract : The partnership decreased the likelihood of misdiagnoses for Iraqi children with cancer and led to more informed Iraqi care providers, thereby improving the care and outcomes of pediatric oncology patients in Iraq.